PELATIHAN KEWIRAUSAHAAN KULINER MELALUI VIDEO EDUKASI DI PONDOK PESANTREN ASY-SYADZILI MALANG - Sari, Padma Adriana (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2021)
Islamic boarding schools have great potential to move the wheels of the economy by producing aspiring entrepreneurs from the thousands of students they have. Knowledge and entrepreneurial skills of Islamic boarding school students need to be continuously honed in order to produce successful entrepreneurs. Therefore, this community service activity contributes to the honing of entrepreneurial skills of students through entrepreneurship training on how to make "Ricebowl" as a culinary product at the Asy-Syadzili Islamic boarding school, Malang Regency. The training is given to the school by providing educational videos, giving tools and ingredients for the practice. The educational video was compiled by lecturers and students from State Polytechnic of Malang.The result of this community service activity is to provide students with insight into entrepreneurship, spur the emergence of business ideas and train skills to create culinary products